Microsoft's Your Phone environment from a digital forensic perspective. (September 2021) - Domingues, Patricio; Andrade, Luis Miguel; Frade, Miguel
Abstract: Your Phone is a Microsoft dual mobile/desktop application that links a Windows 10 environment to a smartphone. The Android version provides the smartphone's user with the ability to control the mobile device from Windows 10, allowing to place/receive calls, send/receive text messages such as SMS, MMS and RCS, access up to the last 2000 photos/screenshots of the device and to receive notifications from applications, all through the Windows 10 Your Phone application and, if configured to do so, within Windows 10 notification center. This work analyzes the Your Phone environment, that is, Your Phone Companion for Android and Your Phone for Windows 10. The paper studies the digital forensic artifacts that can be found in a post mortem analysis, focusing on the SQLite3 databases used by both the Android and Windows 10 applications. We also compare the examined version with a previous version of Your Phone, showing that Your Phone newest functionalities bring new valuable artifacts for forensic examiners. The study shows that Your Phone data left on a Windows 10 device can be useful to access a copy of messages, photos, and document interactions, especially when the Android device is inaccessible or even physically unavailable. To ease the task for digital forensic examiners, we have updated our open-source YPA software that collects and analyzes Your Phone data from a Windows 10 system. YPA runs as a module within the digital forensic Autopsy software. Highlights: Thorough study of Windows 10's Your Phone environment, analyzing Your Phone's digital artifacts left in the computer. Study of Android's Your Phone Companion, covering the digital forensic artifacts of the app. Presentation of the renewed version of Your Phone Analyzer, our open-source module to process Your Phone forensic artifacts.